Republic of Uzbekistan : 2008 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Uzbekistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that the Uzbek economy has performed well in recent years. The favorable external environment and improvements in macroeconomic policies resulted in high growth rates, large current account surpluses, a significant decline in the debt burden, and a more than quadrupling of foreign exchange reserves from 2003 to 2007. Executive Directors have commended the authorities for Uzbekistan's continued strong economic performance, which has benefited from a generally favorable external environment and an improved policy framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet